2003
DOI: 10.1046/j.1440-1746.2003.02922.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lansoprazole, famotidine, roxatidine and rebamipide administration on the urea breath test for the diagnosis of Helicobacter pylori infection

Abstract: Patients showing negative UBT results during the administration of proton pump inhibitors and H2RA should be re-examined after the cessation of these drugs to confirm the true negativity of H. pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 27 publications
1
25
0
1
Order By: Relevance
“…However the results could not be explained by the hypothesis that rebamipide has the function of eliminating H. pylori, even though we have found the H. pylori infection rate in the rebamipide group to be lower than in the sucralfate group. What we can conclude from our study is that rebamipide may improve outcomes of H. pylori-associated gastritis, as previously published [28][29][30][31]. And more long-term, well-designed controlled trials need to be carried out in the future to confirm the drug's relationship with H. pylori status [32].…”
Section: Discussionsupporting
confidence: 70%
“…However the results could not be explained by the hypothesis that rebamipide has the function of eliminating H. pylori, even though we have found the H. pylori infection rate in the rebamipide group to be lower than in the sucralfate group. What we can conclude from our study is that rebamipide may improve outcomes of H. pylori-associated gastritis, as previously published [28][29][30][31]. And more long-term, well-designed controlled trials need to be carried out in the future to confirm the drug's relationship with H. pylori status [32].…”
Section: Discussionsupporting
confidence: 70%
“…Nevertheless, the impact of H 2 -receptor antagonists on the accuracy of 13 C-urea breath test is controversial. Some authors have reported that ranitidine produces the occurrence of false-negative results (71,78,79), whereas others did not show any negative effect on the breath test (73,(80)(81)(82)(83). In any case, studies evaluating both PPIs and H 2 -antagonists in the same population have shown that the false-negative breath test rate caused by H 2 -blockers is far lower than that caused by the administration of a PPI (78).…”
Section: Effect Of Recent Use Of Proton Pump Inhibitors On the Accuramentioning
confidence: 99%
“…This simply reduces the concentration of the gastric bacteria and consequently lowers the delta over baseline (DOB) values. However, PPIs by themselves may also induce false-negative results during diagnostic UBT by an alternative, pH-dependent mechanism [12,13,14]. …”
Section: Introductionmentioning
confidence: 99%